Religious struggles and mental health in the Polish population during the COVID-19 pandemic. Mediation effects of resilience as an "ability to bounce back". Issue 1 (2nd January 2023) - Konaszewski, Karol; Skalski, Sebastian Binyamin; Niesiobędzka, Małgorzata; Surzykiewicz, Janusz
ABSTRACT: The pandemic may manifest itself in the spiritual-existential sphere by activating various forms of religious-spiritual struggles. The purpose of the study was to assess the relationship between religious struggles and mental health in the Polish population during COVID-19. We assumed that the ability to bounce back could minimise the negative impact of religious struggles on mental health therefore we tested the mediating role of resilience as an 'ability to bounce back' in the relationship between these religious struggles and mental health. We also tested the mediating role of resilience as an 'ability to bounce back' in the relationship between religious struggles and mental health. The study involved 688 individuals (74% female) aged 20–68 years. The procedure involved filling out questionnaires to measure resilience, negative religious coping, religious struggles, mental health (depression and mental well-being). The results demonstrated significant relationships between resilience and both mental health indicators. As expected, resilience was a significant mediator of the decreasing effect of religious struggle and negative religious coping on depression and well-being. Resilience as a capacity is valuable for psychosocial functioning of individuals. Strong psychological resources can help protect mental health from religious struggles and negative religious coping.